DNA methylome changes by estradiol benzoate and bisphenol A links early-life environmental exposures to prostate cancer risk. Issue 9 (1st September 2016) - Cheong, Ana; Zhang, Xiang; Cheung, Yuk-Yin; Tang, Wan-yee; Chen, Jing; Ye, Shu-Hua; Medvedovic, Mario; Leung, Yuet-Kin; Prins, Gail S.; Ho, Shuk-Mei
ABSTRACT: Developmental exposure to endocrine-disrupting chemicals (EDCs), 17β-estradiol-3-benzoate (EB) and bisphenol A (BPA), increases susceptibility to prostate cancer (PCa) in rodent models. Here, we used the methylated-CpG island recovery assay (MIRA)-assisted genomic tiling and CpG island arrays to identify treatment-associated methylome changes in the postnatal day (PND)90 dorsal prostate tissues of Sprague-Dawley rats neonatally (PND1, 3, and 5) treated with 25 µg/pup or 2, 500 µg EB/kg body weight (BW) or 0.1 µg BPA/pup or 10 µg BPA/kg BW. We identified 111 EB-associated and 86 BPA-associated genes, with 20 in common, that have significant differentially methylated regions. Pathway analysis revealed cancer as the top common disease pathway. Bisulfite sequencing validated the differential methylation patterns observed by array analysis in 15 identified candidate genes. The methylation status of 7 ( Pitx3, Wnt10b, Paqr4, Sox2, Chst14, Tpd52, Creb3l4 ) of these 15 genes exhibited an inverse correlation with gene expression in tissue samples. Cell-based assays, using 5-aza-cytidine-treated normal (NbE-1) and cancerous (AIT) rat prostate cells, added evidence of DNA methylation-mediated gene expression of 6 genes (exception: Paqr4 ). Functional connectivity of these genes was linked to embryonic stem cell pluripotency. Furthermore, clustering analyses using the dataset from The Cancer Genome Atlas revealed that expression of this set of 7 genes was associated with recurrence-free survival of PCa patients. In conclusion, our study reveals that gene-specific promoter methylation changes, resulting from early-life EDC exposure in the rat, may serve as predictive epigenetic biomarkers of PCa recurrence, and raises the possibility that such exposure may impact human disease.